Towards the Question of Main Components of Minor Paroemia Constructin - Tumanishvili, Khatuna ("Intercultural Dialogues" Transactions, 2025)
A proverb is an integral part of the verbal folklore of a given ethnos - “cast” in the mould of the common national consciousness, which is directly linked with speech (speech in its turn, naturally, is expressive of thinking). Accordingly, it qualitatively (both formally and semantically) is the micro-model of the life and mentality of the world where it was created and where it operates. The present paper aims to interpret the proverb – a formula modeled as a certain concept in a given mentality . On the basis of study of Arabic Syriandialect (with Georgian parallels) material, it is identified how, by what general and at the same time specific means, characteristic of each, the given stereotyped wisdom is created. Conclusions also cover the general theoretical aspect of the problem. On the basis of the analysis of the examples it becomes clear that a proverb comes into being by the simultaneous operation of all the components involved in its creation. Each of them is equally important. The objective reality reflected in them are as usual constructed on specific syntagmatic relations sometimes on the surface level (obviously) and on the deep level (non-obviously) as well. Accordingly they cannot be regarded as mutually independent objects and phenomena, as they are a whole system of regularities being in a certain conceptual connection by means of logical relations. Accordingly, it is possible to understand a proverb only by gaining deep insight into these connections, understanding the regularities found in the historical reality of the given ethnos and by studying the conceptual thinking recorded within the existing mentality. All Arabic examples are recorded and translated from Arabic primary source - directly from Syrian, Lebanese, informants. To avoid possible inaccuracies, for a researcher (not a native speaker of Arabic) interested in studying proverbs the best way proved direct relationship with informants. By re-interpretation in appropriate context, imaginary logical relations established with respect to a particular phenomenon in given ethnoconsciousness (between things and phenomena) were specified. The urgency of this topic is also due to the fact that it is the first attempt to introduce a new topic into Georgian Arabistics.